3D bio-printing of levan/polycaprolactone/gelatin blends for bone tissue engineering: Characterization of the cellular behavior. (October 2019) - Duymaz, Busra Tugce; Erdiler, Fatma Betul; Alan, Tugba; Aydogdu, Mehmet Onur; Inan, Ahmet Talat; Ekren, Nazmi; Uzun, Muhammet; Sahin, Yesim Muge; Bulus, Erdi; Oktar, Faik Nüzhet; Selvi, Sinem Selvin; ToksoyOner, Ebru; et al.
Graphical abstract: Highlights: 3D printed scaffolds of the PCL/GT/HLh blends were successfully fabricated and characterized. This is the first 3D bioprinting study of the levan containing formulations. Significant cell viability was observed. Halomonas levan increased the Hob proliferation. The obtained 3D scaffold had a uniform pore size with homogeneous distribution. Abstract: Poly(ε-caprolactone) (PCL), gelatin (GT) and different concentrations of low molecular weight Halomonas levan (HLh) were combined and examined to develop physical networks serving as tissue scaffolds to promote cell adhesion for biocompatibility. Three-dimensional bioprinting technique (3D bioprinting) was employed during manufacturing the test samples and their comprehensive characterization was performed to investigate the physicochemical properties and biocompatibility. Physical properties of the printing materials such as viscosity, surface tension, and density were measured to determine optimal parameters for 3D bioprinting. The scanning electron microscope (SEM) was used to observe the morphological structure of scaffolds. Fourier-Transform Infrared Spectroscopy (FT-IR) and differential scanning calorimetry (DSC) were used to identify the interactions between the components. In-vitro cell culture assays using standard human osteoblast (Hob) cells showed increased biocompatibility of the printing materials with increasing HLh content. Thus, the formulations including the HLh are expected to be a good candidate for the production of 3D printed materials.